1992
DOI: 10.1029/92gl01157
|View full text |Cite
|
Sign up to set email alerts
|

Inadequacy of effective CO2 as a proxy in assessing the regional climate change due to other radiatively active gases

Abstract: Recent general circulation model (GCM) study suggests that CO2 maintains the present regional climate differently than trace gases CH4, N2O, CFC‐11 and CFC‐12, thus raising the question of the adequacy of using “effective” CO2 to assess future climate changes due to the greenhouse effect of these other radiatively active gases. Our GCM simulations indicate that, although the effective CO2 can provide global mean surface temperature responses in good agreement with that when these other trace gases are explicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…In agreement with the previous studies [Wang et al, 1991[Wang et al, , 1992] the results presented here indicate that trace gases and equivalent CO2 produce different patterns of surface, tropospheric and stratospheric temperature change, which are significant at a 5% level. However, in contrast to their results, we find that the global annual-mean response also differs by as much as 20%.…”
Section: Discussionsupporting
confidence: 81%
“…In agreement with the previous studies [Wang et al, 1991[Wang et al, , 1992] the results presented here indicate that trace gases and equivalent CO2 produce different patterns of surface, tropospheric and stratospheric temperature change, which are significant at a 5% level. However, in contrast to their results, we find that the global annual-mean response also differs by as much as 20%.…”
Section: Discussionsupporting
confidence: 81%
“…Halocarbons and ozone changes may not fit this simple constant-sensitivity picture. Climate models typically show different responses to equivalent forcings from WMGHG changes and CO 2 (Wang et al, 1991(Wang et al, , 1992Govindasamy et al, 2001). In particular, Hansen et al (1997) found halocarbons to have a ∼20% larger climate sensitivity than CO 2 , mainly due to a stronger positive cloud feedback in their halocarbon experiments.…”
Section: Climate Sensitivitymentioning
confidence: 99%
“…This, combined with a typical vertical temperature profile, means that halocarbons usually warm the atmosphere locally, as opposed to carbon dioxide, which generally cools (the atmosphere only warms as a response to the induced surface warming). Further, this effect is largest at the tropical tropopause, where temperatures are most different from those of the underlying surface (e.g., Dickenson, 1978;Wang et al, 1992;Forster et al, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…In addition to calculating the response of climate to ozone changes, the impact of a homogeneous change in methane is also computed because, as explained earlier, methane is affected by the changed emissions. We are not aware of other GCM calculations of the climate sensitivity to methane changes alone; Wang et al (1991, 1992) and Govindasamy et al (2001) have compared the climate sensitivity to increases in a range of well‐mixed greenhouse gases, compared with equivalent CO 2 , with conflicting conclusions. Wang et al (1991, 1992) showed that the global‐mean sensitivity is similar in both cases, while Govindasamy et al (2001) found that explicit consideration of the well‐mixed gases led to a 20% increase in climate sensitivity.…”
Section: Surface Temperature Response and Climate Sensitivitymentioning
confidence: 99%